PENGARUH FAKTOR KEPRIBADIAN WIRAUSAHA TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA AKUNTANSI Studi pada mahasiswa Akuntansi Universitas Ahmad Dahlan Yogyakarta - Barata, Budi; Fachrudin, Kurniawan Ali (Universitas Ahmad Dahlan, 2013)
Many studies suggest that personality factors determining the entrepreneurship intentions. On the other hand, entrepreneurship education is one way to increase student entrepreneurship intentions. Another personality factor that can improve student entrepreneurship intention is risk-taking propensity and locus of control. The purpose of this study is to find empirical evidence about the influence of personality factors as seen from education entrepreneurship, risktaking propensity, and locus of control on entrepreneurial intentions of students of the Faculty of Economics of Accounting Studies Program University of Ahmad Dahlan Yogyakarta. The data used are primary data where the sample was taken based on purposive sampling as many as 100 students of Accounting Ahmad Dahlan University Yogyakarta. Regression analysis was usedÂ toÂ testÂ research hypotheses with the help of SPSS 16. Research results showed that entrepreneurship education and locus of control affect the entrepreneurial intention, while the trend did not affect the risk-taking entrepreneurial intentions. Based simultaneous test (F test) variables entrepreneurship education, risk taking propensity, locus of control and influence on entrepreneurial intentions.